2022
DOI: 10.1007/s40299-022-00663-4
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Distance Education: Evaluation in the Context of Twenty-first Century Skills

Abstract: In this study, we aimed to investigate the prospective primary school teachers’ opinions about their experiences in distance education within the scope of twenty-first century skills during COVID-19 pandemic. The phenomenological research method was used for the purpose of enlightening this specific context. The study group involved 16 prospective primary school teachers. Data were collected through semi-structured interviews. The credibility of the data were provided by obtaining the consent of the participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Although there are many studies found in the perspective of implementing 21st century skills and its adaptation, there is still a gap, where less research is done on identifying and improving new set of skills for the 21st century. Many studies have been carried out to focus on the development of 21st century skills (Hernandez & Santos, 2017;Publica, 2017) in fact, implementation studies for 21st century skills have also been carried out around the world such as the Netherlands (Van & Voogt, 2018;Tsangaratou & Rotterdam, 2022); Singapore Loh & Teo, 2019), the Philippines (Barrot, 2019;Gopo, 2022), China (Cai et al, 2017), Turkey (Sumen & Calisici, 2017;Bozgun et al, 2022;Ozen, 2022), Italy (Gratani & Giannandrea, 2022), France (Celuma & Maoulida, 2022), the United States (Chu et al, 2017) as well as European Union countries and OECD countries (Bakay, 2022). As a matter of fact, this area of study has also been carried out by Latin American countries except Costa Rica (Bujanda et al, 2018) based on (Jimena, 2021).…”
Section: Problem Statementmentioning
confidence: 99%
“…Although there are many studies found in the perspective of implementing 21st century skills and its adaptation, there is still a gap, where less research is done on identifying and improving new set of skills for the 21st century. Many studies have been carried out to focus on the development of 21st century skills (Hernandez & Santos, 2017;Publica, 2017) in fact, implementation studies for 21st century skills have also been carried out around the world such as the Netherlands (Van & Voogt, 2018;Tsangaratou & Rotterdam, 2022); Singapore Loh & Teo, 2019), the Philippines (Barrot, 2019;Gopo, 2022), China (Cai et al, 2017), Turkey (Sumen & Calisici, 2017;Bozgun et al, 2022;Ozen, 2022), Italy (Gratani & Giannandrea, 2022), France (Celuma & Maoulida, 2022), the United States (Chu et al, 2017) as well as European Union countries and OECD countries (Bakay, 2022). As a matter of fact, this area of study has also been carried out by Latin American countries except Costa Rica (Bujanda et al, 2018) based on (Jimena, 2021).…”
Section: Problem Statementmentioning
confidence: 99%
“…The current practice of online education is a manifestation of the practice of remote emergency education during the COVID-19 pandemic (Bozgun et al, 2022;Ndzinisa & Dlamini, 2022). However, the online education practice that is suddenly applied can affect learning performance.…”
Section: Introductionmentioning
confidence: 99%